رأي علماء الكلام في الإعجاز من خلال ثنائية اللفظ والمعنى - بوخزنة, حمزة (University of Eloued جامعة الوادي, 2017)
تناولت هذه المقالة أحد أهم القضايا، وهي قضية اللفظ والمعنى. التي كان لمسألة الإعجاز دور في إثرائها من خلال ما قدّمه علماء الكلام من آراء كل وفق أصوله الاعتقادية ومرجعياته المذهبية. وقد خلصت إلى أنّ البحث في إعجاز القرآن كان له دور كبير في إثارة كثير من القضايا التي لعبت دورا بارزا في صياغة مفاهيم جديدة كان لها فيما بعد أثر في العديد من المجالات خاصة قضايا الأدب والنقد واللغة والبلاغة. Abstract This research deals with one of the most important issues, namely the issue of term and meaning, that the question of inimitability had a role in enriching it through the views of Islamic Theology scholars. Hence, the search in the inimitability of the Koran had a major role in raising a lot of issues that played a prominent role in the formulation of new concepts reflected especially on issues of literature, criticism, language and rhetoric
Opinion of Islamic Theology scholars for the inimitability through bilateral term and meaning
مجلة البحوث والدراسات المجلد 14 العدد 01 جامعة الوادي
Keywords: الإعجاز – القرآن – اللغة – علم الكلام; inimitability - the Koran - Language - theology